Pengaruh Bimbingan Layanan Pendamping Terhadap Peningkatan Kemampuan Penulisan Artikel Jurnal Online Mahasiswa Fakultas Keperawatan Universitas Riau - Thamrin Hasan; Nela Hariza Novriani; Yurnalis; Asmawati (Perpustakaan Universitas Riau, 2023)
Writing is one of the skills in language. The writing aspect must be understood in addition to listening, speaking and reading skills. Writing is a process, meaning that writing skills will be obtained properly through the intensity of the exercises carried out. Without practicing and not understanding the rules of the language, writing skills will not be realized properly. The purpose of this study was to determine the effect of companion service guidance on improving skills in writing online journals. The research method is a quasi-experimental design, using the Nonequivalent Control Group Design. Respondents amounted to 50 students. Research instruments in the form of pre-test and post-test. Data analysis techniques used are descriptive statistical analysis techniques and inferential statistical analysis. The results showed that there was an effect of the implementation of mentoring services on improving the ability to write online journal articles for students, with a correlation coefficient of 0.632. The value of this correlation coefficient indicates that the level of strength of the relationship is strong. There is an influence on the implementation of companion guidance on increasing the ability to write student online journal articles (JOM). Assistance service guidance significantly determines and contributes 5.40% to improving students' ability to write online journal articles. It can be concluded that increasing the ability to write online journal articles for students can be improved through the implementation of escort service guidance. Based on this explanation, it can be seen that the proposed research hypothesis is acceptable.